Cost-efficient payoffs under model ambiguity - Carole Bernard; Gero Junike; Thibaut Lux; Steven Vanduffel (Finance and Stochastics, 2024)
Abstract Dybvig ( 1988a , 1988b ) solves in a complete market setting the problem of finding a payoff that is cheapest possible in reaching a given target distribution (“cost-efficient payoff”). In the presence of ambiguity, the distribution of a payoff is, however, no longer known with certainty. We study the problem of finding the cheapest possible payoff whose worst-case distribution stochastically dominates a given target distribution (“robust cost-efficient payoff”) and determine solutions under certain conditions. We study the link between “robust cost-efficiency” and the maxmin expected utility setting of Gilboa and Schmeidler ( 1989 ), as well as more generally in a possibly nonexpected robust utility setting. Specifically, we show that solutions to maxmin robust expected utility are necessarily robust cost-efficient. We illustrate our study with examples involving uncertainty both on the drift and on the volatility of the risky asset.
Additional information: C02;C63;D80
Keywords: 330; Cost-efficient payoffs; Model ambiguity; Maxmin utility; Robust preferences; Drift and volatility uncertainty